An educational computer program for matrix analysis of plane trusses in civil engineering (2023)
An educational computer program called Armadura2D was developed for matrix analysis of plane trusses, which is intended for engineering students. The program has a great advantage over commercial software, since it is designed to assist step-by-step matrix analysis of plane trusses calculation; this is essential for the lessons of the Structure Analysis course, in the civil engineering undergraduate program. This paper provides a conceptual and mathematical model, a pseudocode of the computational model developed in FORTRAN, the verification of the accuracy of the computer program with a classic problem extracted from a classical book [1] and results are compared with Ansys® simulation software. In conclusion, this application is an alternative support that enhances the traditional teaching-learning process inside classrooms, and the autonomous learning of civil engineering students of the matrix analysis, particularly for plane trusses. © 2006-2020 Asian Research Publishing Network (ARPN).